2017
DOI: 10.1371/journal.pone.0178654
|View full text |Cite
|
Sign up to set email alerts
|

Associations of low-intensity light physical activity with physical performance in community-dwelling elderly Japanese: A cross-sectional study

Abstract: BackgroundPhysical activity and physical performance relate to quality of life, mortality, and morbidity in elderly people. However, little is known about differences in physical performance related to low-intensity light physical activity (LLPA), high-intensity light physical activity (HLPA), and moderate-intensity physical activity (MPA) and how they are separated by sex in elderly populations.AimsThis study aimed to determine differences in LLPA, HLPA, MPA, and physical performance, and associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
2
25
3
1
Order By: Relevance
“…Our finding that physical activity of any intensity was beneficially associated with walking speed over both long and short distance is remarkable, since performance in walking tests predicts disability, mobility limitation and deaths [35]. The association of moderate-to-vigorous-intensity activity with walking speed was expected and in line with previous cross-sectional studies (10)(11)(12)(13). In contrast, light-intensity activity has been beneficially Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our finding that physical activity of any intensity was beneficially associated with walking speed over both long and short distance is remarkable, since performance in walking tests predicts disability, mobility limitation and deaths [35]. The association of moderate-to-vigorous-intensity activity with walking speed was expected and in line with previous cross-sectional studies (10)(11)(12)(13). In contrast, light-intensity activity has been beneficially Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Correlations are adjusted by sex and age associated with walking speed in some [10], but not all [9,11] studies. One study found a significant association only in women [13]. In the present study, the associations of time spent in light activity with 6-min walk and 10-m walk were statistically significant even after adjusting for time spent in moderate-to-vigorous intensity activity suggesting that light-intensity activity has an independent positive association with walking speed.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Meanwhile, the value of the contribution of light physical activity to health has become recognized in recent years [32,38]. As a result of a several studies conducted by categorizing low-intensity physical activity of less than 3.0 METs into either low-intensity light physical activity (LLPA) of 1.6 METs or more and less than 2.0 METs, or high-intensity light physical activity (HLPA) of 2.0 METs or more and less than 3.0 METs, HLPA has been reported to improve insulin resistance, activity as mild as walking has been reported to have led to reduced severity of stroke events, and these activities have been partially correlated with physical functions in elderly Japanese women [38][39][40]. Furthermore, a study by Buman et al [41] demonstrated that HLPA contributes to health to the same degree as moderate physical activity and also contributes greatly to subjective life satisfaction.…”
Section: Discussionmentioning
confidence: 99%